Risk behavior to STD and HIV infection among university professors - Jacobowski, Bruna; Jung, Gustavo S.; Trevisol, Fabiana Schuelter (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: there is increased HIV infection among heterosexual couples, even in stable and faithful relationships. Objective: to assess sexual behavior and risk to acquiring sexually transmitted diseases (STDs) and human immunodeficiency virus (HIV) among health area faculty working at a university in southern Brazil. Methods: cross-sectional study conducted between December 2009 and March 2010. Health area faculty members working at a university in southern Brazil were included in the survey. Upon approval, anonymous and self-administered questionnaire was used, which included data on sociodemographic characteristics, risk sexual behavior for exposure to HIV and STDs, as well as additional risk factors to diseases acquired intravenously. Statistical analysis was performed using the SPSS, version 16.0. Results: a total of 184 faculty members was studied; 55.4% were women. Mean age was 40.5 (SD ± 9.1) years. Anal sex, larger number of partners, higher sex frequency, and infidelity was associated with being male. Of the interviewees, 31% reported infidelity; only 19.8% used condoms in marital relations and 39.3% in extramarital sex. Condom use was associated with infidelity. Among other risk factors, 39.1% reported having shared personal hygiene objects, 3.8% had undergone blood transfusion, 11.4% had a tattoo or piercing, and 31% had already had work-related needlestick accidents. Conclusion: the sample studied is at risk of contracting HIV and other STDs because of poor or inconsistent condom use, high prevalence of extramarital relationships, alcohol use before sexual intercourses, anal sex, multiple partners, and high rates of work-related needlestick injuries.